Analysis of Compliance Levels and Quality of Life Perspectives for Outpatient Hypertension Patients at Hospital X, Mojokerto Regency - Anis Akhwan Dhafin; Fendy Prasetyawan; Elsa Mahardika Putri; Muhammad Alviyan Shutiawan; Okky Intan Mawarni; Faisal Akhmal Muslikh (MultiTech Publisher, 2023)
The incidence of hypertension in the world in 2021 is estimated at 1.28 billion adults worldwide suffering from hypertension and 3 million of them die every year. Seven out of ten sufferers do not receive treatment. Hypertension sufferers in East Java in 2021 aged over 15 years are estimated to be 11,686,430, with a total of 48.38% men and 51.62% women. Of this number, 9.70% of hypertension sufferers received treatment. Low compliance with taking medication causes hypertension to get worse and will affect the quality of life of someone suffering from hypertension. This research is a prospective quantitative research using a cross sectional research design. Using a side sampling technique. The number of samples in the study was 100 patients. The results of this study showed that the highest level of medication adherence was in the medium category at 61%, high 31% and low 9%. The level of quality of life for hypertensive patients in the moderate category is 56%, low 35% and high 9%.